Direct current magnetic field: An optional strategy for reducing pyrophosphate in gelatinous meat products. (1st November 2022) - Yang, Kun; Wu, Di; Wang, Limei; Wang, Xian; Ma, Jing; Sun, Weiqing
Abstract: This study was to investigate effects of direct-current magnetic field (DC-MF) and tetrasodium-pyrophosphate (TSPP) on properties of myofibrillar protein (MP) gels, to understand potential mechanisms of action, and to clarify feasibility of TSPP reduction by applying DC-MF. MP was either untreated or treated with DC-MF (9.5 mT) and TSPP (0–5 g/L) for 3 h, and then heat-induced gel was prepared for further analysis. Secondary structure, microstructure and water distribution of MP gels were measured respectively by Raman spectroscopy, scanning-electron-microscopy and low field NMR. The relationship between gel properties and protein structure was visualized by PCA. WHC obviously increased, while hardness, fracture and apparent viscosity became lower under DC-MF and high-level TSPP, with more significant effect on WHC, hardness and fracture as TSPP level changed than DC-MF. The texture of gels treated by DC-MF and 3 g/L TSPP was indistinguishable from that of 5 g/L control, delightfully, with TSPP usage decreasing from 5 to 3 g/L. DC-MF and TSPP could affect MP gel hydration ability by influencing microstructure, the content of α-helix and β-sheet, and exposing side-chain-residues. Gel texture was strongly correlated with random coil and β-turn. Overall, DC-MF and TSPP affected gel properties by altering protein and gel structure, DC-MF might be considered an optional strategy for reducing pyrophosphate in gelatinous meat products. Highlights: Phosphate (TSPP) and magnetic field (DC-MF) had synergistic effects on gel texture. 3 g/L phosphate with DC-MF achieved 40% TSPP reduction while maintaining texture. DC-MF had potential applications in phosphate reduction of meat products.